2003
DOI: 10.1002/anie.200351496
|View full text |Cite
|
Sign up to set email alerts
|

Metallaoxetanes and Carbenes from Diolates in High‐Valent Rhenium Oxo Chemistry: The Importance of the Coordination Number

Abstract: We report an electrospray ionization tandem mass spectrometric study of the chemistry of Re V diolate complexes in which the intermediacy of the isomeric metallaoxetane complexes is implicated by dissociation of the diolates to rhenium carbene complexes instead of the expected oxo species (Scheme 1). Not only is the chemistry unprecedented for well-defined diolate complexes, but the marked dependence of the preferred reaction path upon coordination number in the original diolate complex supports a qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…[7] More recent studies have shown that rhenium alkylidene complexes can be generated from the corresponding glycolate through an oxarhenacyclobutane, suggesting that the pseudoWittig pathway can indeed be a viable pathway of initiation. [15][16][17] Here below, a combined reactivity study of various olefins with Re 2 O 7 /Al 2 O 3 shows that this catalyst contains only 2 % of active sites, and the propagating alkylidene does not need to be formed through a p-allyl intermediate, so that the pseudoWittig reaction is a preferred initiation mechanism. , [7] and shows that propene can generate the propagating carbene, while ethene cannot [Eqs.…”
Section: Introductionmentioning
confidence: 98%
“…[7] More recent studies have shown that rhenium alkylidene complexes can be generated from the corresponding glycolate through an oxarhenacyclobutane, suggesting that the pseudoWittig pathway can indeed be a viable pathway of initiation. [15][16][17] Here below, a combined reactivity study of various olefins with Re 2 O 7 /Al 2 O 3 shows that this catalyst contains only 2 % of active sites, and the propagating alkylidene does not need to be formed through a p-allyl intermediate, so that the pseudoWittig reaction is a preferred initiation mechanism. , [7] and shows that propene can generate the propagating carbene, while ethene cannot [Eqs.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the use of transition metal complexes as catalysts also opens the possibility of efficient asymmetric olefination [4,5]. Accordingly, several catalytic aldehyde and ketone olefination systems have been reported based on Mo [6,7], Re [8][9][10][11][12][13][14][15], Ru and Rh [16][17][18][19][20][21][22], Fe [20,[23][24][25][26][27] and Co [28] complexes.…”
Section: Introductionmentioning
confidence: 98%
“…[32] Indeed, the reaction of several strained cyclic olefins, such as norbornene, dicyclopentadiene (DCPD), and cyclooctene, with a 0.1-0.2 % load of the catalysts 2 a or 2 b in chlorobenzene at room temperature, produced polymers of high molecular weight and with a surprisingly high Z content of the olefin groups in the polymer backbone (Table 1). The Z-olefinic content in ROMP polymers is usually low.…”
mentioning
confidence: 99%
“…However, defined soluble rhenium complexes have rarely exhibited high activity. A few catalysts are known with rhenium in a high oxidation state; [32] systems with rhenium in a low oxidation state have not been studied, except for a dinuclear rhenium-carbonyl complex activated with iBuAlCl 2 . [33,34] We therefore focused on the development of novel rhenium-based olefin metathesis catalysts.…”
mentioning
confidence: 99%